2020
DOI: 10.1186/s12905-020-01104-4
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between traumatic brain injury and intimate partner violence: data driven analysis utilizing electronic health records

Abstract: Background It is estimated that a majority of intimate partner violence (IPV) victims suffer from blunt force to the head, neck and the face area. Injuries to head and neck are among the major causes for traumatic brain injury (TBI). Methods In this interdisciplinary study, we aimed to characterize the key associations between IPV and TBI by mining de-identified electronic health records data with more than 12 M records between 1999 to 2017 from the IBM Explorys platform. For this purpose, we formulated a dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 42 publications
1
10
0
1
Order By: Relevance
“…Over a third of women (36.4%) experience psychological aggression and about 41% of female survivors experience some form of physical injury during their lifetime (NISVS, 2012). Acute injuries including bruises, fractures, sensory damage, and internal injury, in addition to long term ailments such as muscle-skeletal issues and metabolic issues, are significantly more common among the victims of IPV than nonvictims (Krug et al, 2002;Kilpatrick et al, 2003;Karakurt et al, 2017;Liu et al, 2020).…”
Section: Effectiveness Of Treatments For Adverse Effects Of Intimate ...mentioning
confidence: 99%
“…Over a third of women (36.4%) experience psychological aggression and about 41% of female survivors experience some form of physical injury during their lifetime (NISVS, 2012). Acute injuries including bruises, fractures, sensory damage, and internal injury, in addition to long term ailments such as muscle-skeletal issues and metabolic issues, are significantly more common among the victims of IPV than nonvictims (Krug et al, 2002;Kilpatrick et al, 2003;Karakurt et al, 2017;Liu et al, 2020).…”
Section: Effectiveness Of Treatments For Adverse Effects Of Intimate ...mentioning
confidence: 99%
“…Increased awareness of TBI among IPV survivors and increased awareness of the associated adverse health outcomes are crucial ( Gerber et al, 2014 ; St Ivany and Schminkey, 2016 ; Liu et al, 2020 ). Our results indicated that certain relationship dynamics such as threats and severe violence are more common among survivors of IPV with head trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Women exposed to physical IPV are more likely to experience psychological distress and cognitive dysfunction relating to brain injury, with one study estimating nearly 75% of survivors may have sustained one or more partner-related brain traumas, where injury severity is negatively associated with cognitive function (i.e., learning, memory, cognitive flexibility) and positively associated with abuse severity and PTSD symptomatology ( Woods, 2000 ; Valera and Berenbaum, 2003 ; Woods et al, 2008 ; Davis, 2014 ; St Ivany and Schminkey, 2016 ; Iverson et al, 2017 ; Campbell et al, 2018 ; Esopenko et al, 2021 ). Women who experience IPV-related TBI are at a heightened risk of worse long-term psychosocial health outcomes, and while some research shows that TBI severity is related to depression and anxiety but independent of PTSD, many studies suggest improved IPV-specific screening tools are critical for more accurate and effective patient care ( Gerber et al, 2014 ; Iverson and Pogoda, 2015 ; Goldin et al, 2016 ; Murray et al, 2016 ; St Ivany and Schminkey, 2016 ; Amoroso and Iverson, 2017 ; Cimino et al, 2019 ; Iverson et al, 2019 , 2020 ; Smirl et al, 2019 ; Haag et al, 2019a , b ; Liu et al, 2020 ; Fortier et al, 2021 ; Meyer et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…With all that said, there are several symptoms that are common among women experiencing TBI because of domestic violence. These symptoms include malnutrition, alcoholic cirrhosis, acquired thrombocytopenia, and post-traumatic wound infection [ 37 ]. It is important that healthcare workers can identify these symptoms and associate them with a possible result of abuse, indicating that the patient may need to be screened for TBI.…”
Section: Diagnosis Of Tbi Secondary To Domestic Violencementioning
confidence: 99%